Evaluasi Infrastruktur Laboratorium Multimedia Universitas ‘Asiyiyah Surakarta dengan Metode COBIT 5.0 - Yuninda Tri Desianti; Bekti Setiyaningrum; Rivaldo Helitona; Azka Nur Azizah (Universitas Aisyiyah Surakarta, 2026)
College continues to seek to provide a representative learning tool, one of which is through multimedia laboratories. In ‘Aisyiyah University of Surakarta (AISKA), multimedia laboratories are utilized mainly for S1 system and information technology studies students, although their use is also open to students from other programs when needed. The laboratory is equipped with such devices as computers, projectors, and air-conditioning that support academic activities, especially technology-based practices and learning. The study evaluates the quality and worthiness of the laboratory's infrastructure by referring to the COBIT 5.0 framework that focuses on information technology governance. The data is collected through interviews with those involved, including active users and laboratory managers. The study's findings indicate that while the available facilities are sufficiently supportive, several aspects still need repair, especially regarding asset maintenance and management. This evaluation concludes that laboratory management must be continually improved to be able to adapt to dynamic technological development and academic needs.